Metabolic Syndrome in Schizophrenia - Ghimire, SR; Rai, Y (Journal of Psychiatrists' Association of Nepal, 2018)
Metabolic syndrome (MS), a constellation of interconnected metabolic disorders including obesity (central and abdominal), hyperglycemia, dyslipidemias and hypertension is highly prevalent among patients with schizophrenia. The prevalence of MS varies across countries and ethnic groups. There are multiple determinants of MS among patient with schizophrenia, important being age, sex, ethnic group, longer duration of illness, advanced age, and use of antipsychotics. Early detection and management of metabolic abnormalities could prevent associated premature morbidity and mortality in schizophrenia. Future research is needed to identify and explore genetic determinants of MS in schizophrenia which could help to prevent and manage the illness in better way. J Psychiatrists’ Association of Nepal Vol .6(1), 2017, p.3-11